2016
DOI: 10.1002/nau.23135
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications of conduit urinary diversion with concomitant cystectomy for benign indications: A population‐based analysis

Abstract: AIMS Beyond single-institution case series, limited data are available to describe risks of performing a concurrent cystectomy at the time of urinary diversion for benign end-stage lower urinary tract dysfunction. Using a population-representative sample, this study aimed to analyze factors associated with perioperative complications in patients undergoing urinary diversion with or without cystectomy. METHODS A representative sample of patients undergoing urinary diversion for benign indications was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Although not statistically significant, patients with RC+conduit UD were more likely to die than those undergoing conduit UD alone. This is consistent with previous work using the Nationwide Inpatient Sample (NIS), which showed that the addition of RC to UD for strictly benign etiologies led to higher rates of complications during the post-operative hospitalization (OR 1.23, 95% CI 1.03-1.48) (13).…”
Section: Discussionsupporting
confidence: 91%
“…Although not statistically significant, patients with RC+conduit UD were more likely to die than those undergoing conduit UD alone. This is consistent with previous work using the Nationwide Inpatient Sample (NIS), which showed that the addition of RC to UD for strictly benign etiologies led to higher rates of complications during the post-operative hospitalization (OR 1.23, 95% CI 1.03-1.48) (13).…”
Section: Discussionsupporting
confidence: 91%
“…The management of such conditions is primarily achieved by conservative and/or minimally invasive measures. If these measures fail, surgical interventions are indicated (7,8,14,15). These surgical interventions, however, have a significant impact on patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In selected cases cystectomy and urinary diversion has been described as a last resort for refractory lower urinary tract dysfunction secondary to neurogenic bladder (e.g., spinal cord injury, spina bifida, and multiple sclerosis are common indications), radiation cystitis, interstitial cystitis, or recurrent fistula formation 1,2 as well as devastated bladder outlet after prostatectomy. 3 The European Association of Urology (EAU) Guidelines describe urinary diversion as a reconstructive option for patients with intractable urinary incontinence after multiple pelvic procedures, radiotherapy or pelvic pathology leading to irreversible sphincteric incompetence or fistula formation.…”
Section: Introductionmentioning
confidence: 99%